2017
DOI: 10.1002/crq.21195
|View full text |Cite
|
Sign up to set email alerts
|

The Moral Order in Family Mediation: Negotiating Competing Values

Abstract: We used discourse analysis to study how mediators and parties negotiate competing priorities and values during the family mediation process. We drew on understandings of practical morality, specifically the concept of a moral order, to study UK mediation session talk. Our analysis highlighted the contradictory moral orders drawn on by parties and mediators. The saliency of moral categories and concerns in parenting is demonstrated, and we consider the problems this causes in the “no‐fault” context of mediation. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
0
3
0
4
Order By: Relevance
“…Greatbatch and Dingwall () showed how such narratives could influence family mediation where mediators suggested that domestic violence claims remained outside the scope of the mediation. Smithson, Barlow, Hunter, and Ewing () also discussed family mediations where clients tried to assert, “the demonstrable moral order” informing a relationship (p. 189). Mediators, in this case, referred to the common mediation narratives around turn‐taking, respect, and so forth.…”
Section: Resultsmentioning
confidence: 99%
“…Greatbatch and Dingwall () showed how such narratives could influence family mediation where mediators suggested that domestic violence claims remained outside the scope of the mediation. Smithson, Barlow, Hunter, and Ewing () also discussed family mediations where clients tried to assert, “the demonstrable moral order” informing a relationship (p. 189). Mediators, in this case, referred to the common mediation narratives around turn‐taking, respect, and so forth.…”
Section: Resultsmentioning
confidence: 99%
“…Today, various entities provide standards of practice for mediators. For instance, Smithson and colleagues note that a key element of mediator training is highlighting the “importance of neutral or impartial facilitation” (Smithson et al , 2017, p. 173). The Model Standards of Conduct for Mediators (American Bar Association, 2005, np) suggests that sometimes mediators also have an obligation to “balance…party self-determination with a mediator’s duty to conduct a quality process.” This expectation is particularly relevant where histories of coercive control or IPV may exist (Field, 2016).…”
Section: Family Law Mediationmentioning
confidence: 99%
“…El primer grupo, ha comprendido las obras de Hoffman ( 2011 El segundo grupo, ha sido vertebrado por un 13,3% de propuestas de investigación que han hecho uso de la técnica de recogida de datos basadas en encuestas o cuestionarios (Armadans et al, 2015;Bollen & Euwema, 2015); un 6,6% los registros observacionales (Glenn, 2010) y; un 33,3% las técnicas cualitativas basadas en el análisis del discurso (Jameson et al, 2010;Britton & Johnson, 2016;Howieson & Iriks, 2017;Smithson et al, 2017) o el grupo de discusión (Picard & Siltanen, 2013).…”
Section: Análisis Crítico De Los Artículos Que Forman Parte De La Revisiónunclassified
“…Trabajo Social Global -Global Social Work, Vol 10, nº 18, enero-junio 2020, 23-45 uso de las preguntas transformadoras y las preguntas centradas en la solución (Barthel & Fortson-Harwell, 2016); la comprensión de los objetivos y las características del conflicto que ha traído a las partes a mediación (Berman-Robinson & Shurven, 2016); la atención a los roles de género (Britton & Johnson, 2016); la suspensión del juicio (Smithson et al, 2017) y; herramientas como el Caucus (Hoffman, 2011;Howieson & Iriks, 2017), como elementos que favorecen la generación de comprensión de la persona mediadora para con las partes.…”
Section: Análisis Crítico De Los Artículos Que Forman Parte De La Revisiónunclassified
See 1 more Smart Citation